Maritime Security in International Law: A Conceptualization - Leszek KURNICKI (Communications of International Proceedings, 2022)
The article substantiates the necessity to develop and adopt a unified concept of maritime security as a basis for the development of international law. The “hard” and “soft” challenges to maritime security are considered, including maritime piracy; maritime terrorism; proliferation of weapons of mass destruction by sea; maritime drug trafficking; illegal transportation of migrants by sea; illegal, unreported and unregulated fishing; pollution of the sea and sea coast. The threats to maritime security are closely interrelated. However, international law aimed at ensuring maritime security is not sufficiently consistent and systematized. There is a number of uncertainties and ambiguities in the international legal acts. Coastal states and regional organizations are trying to fill in some gaps in international maritime law. These attempts cannot be successful because of discrepancies between legal acts of different states and regional organizations.
Keywords: international law; law of the sea; marine environment; maritime piracy; maritime security; safety of navigation.